Customer Satisfaction with Pharmacist Services inWest Jakarta - Kasianto Kasianto; Veraladeska Veraladeska; Priyanto Priyanto (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates customer satisfaction with pharmacist services in West Jakarta, employing the SERVQUAL model to assess service quality across five dimensions: reliability, responsiveness, assurance, empathy, and tangibles. A quantitative survey was conducted with 250 respondents, including pharmacy customers and accompanying family members, using a structured questionnaire based on a five-point Likert scale (1 = Very Dissatisfied to 5 = Very Satisfied). Validity and reliability tests confirmed the instrument’s accuracy and consistency. Results indicate that overall customer satisfaction falls within the “Satisfied” category, with an overall mean score of 2.86 on a 1–4 Likert scale. Reliability scored the highest (2.94), reflecting customer satisfaction with pharmacists’ accuracy and consistency in service delivery, followed by Assurance (2.88), demonstrating confidence in professionalism, knowledge, and competence. Empathy received a mean score of 2.81, indicating adequate personal attention, while Responsiveness and Tangibles scored the lowest (both 2.78), highlighting areas requiring improvement in service speed, waiting area comfort, cleanliness, and staff appearance. Item-level analysis revealed that approximately 29% of responses fell within the “Dissatisfied” category, primarily related to waiting times, responsiveness, and physical facilities. These findings suggest that while pharmacist services in West Jakarta are generally satisfactory, targeted improvements in responsiveness and tangibles are necessary to elevate service quality and achieve “Very Satisfied” levels. The study provides evidence-based recommendations for enhancing pharmacist- customer interactions, optimizing physical facilities, and strengthening the professional image of pharmacists in urban pharmacy settings.